What does the future hold for cholesteryl ester transfer protein inhibition?. Issue 6 (December 2015) - Arsenault, Benoit J.; Boyer, Marjorie; Kastelein, John J.P.
Abstract : Purpose of review: This article summarizes the latest studies relevant to cholesteryl ester transfer protein (CETP) inhibition and cardiovascular risk and proposes a series of patient populations that might eventually derive benefits from CETP inhibition. Recent findings: Results of recently published genetic epidemiology studies have helped shape our understanding of the association between lipoprotein–lipid levels and cardiovascular disease risk. These studies have confirmed the proatherogenic role of apolipoprotein B-containing lipoproteins and triglycerides and renewed our interest for lipoprotein(a) as a significant and causal predictor of cardiovascular risk. The association between HDL cholesterol levels and cardiovascular risk, albeit strong and consistent, is unlikely to be of causative nature, at least according to genetic epidemiology. However, a handful of intriguing studies have highlighted a predictive role for HDL cholesterol efflux capacities in predicting cardiovascular risk independently of HDL cholesterol levels. Potent CETP inhibitors, currently under investigation, significantly decrease apolipoprotein B-containing lipoproteins and lipoprotein(a) and increase both HDL cholesterol levels and HDL cholesterol efflux capacities. Summary: Two phase 3 cardiovascular outcomes trials testing the hypothesis that CETP inhibition will reduce cardiovascular outcomes in high-risk patients are well underway. The future of CETP inhibition will depend on the outcomes of these trials.